Body composition and nutritional status changes in adolescents with anorexia nervosa - Mercedes Murray Hurtado; Álvaro Martín Rivada; Carlos Quintero Alemán; María Pilar Ruiz Alcántara; Yolanda Ramallo Fariña (Elsevier, 2023)
Introduction: Nutritional status assessment in anorexia nervosa (AN) includes the evaluation and monitoring of body composition throughout the treatment period. The gold standard for the study of body composition is dual-energy X-ray absorptiometry (DEXA), although electrical bioimpedance (BIA) is a more accessible, cheaper and faster method that does not involve exposure to radiation. Material and methods: We recruited 33 female adolescents with AN (age, 11.7-16.3 years) by consecutive sampling. We collected data on clinical, anthropometric and laboratory variables. Patients were assessed with BIA and DEXA at inclusion in the study and at the end of the study, with a mean duration of follow-up of 1 year, during the nutritional rehabilitation phase. Results: There was significant improvement in nutritional status, reflected by the body composition obtained by anthropometric measurements and BIA. The phase angle increased significantly during the follow-up. Greater weight loss was associated with the presence of secondary amenorrhoea and decreased bone mineral density in the spine. Conclusions: Electrical BIA is a useful tool for assessment and monitoring of nutritional status in paediatric patients with AN. Dual-energy X-ray absorptiometry continues to be essential to assess bone mineral density. The role of hormones such as leptin remains to be elucidated. Resumen: Introducción: La valoración nutricional en anorexia nerviosa (AN) incluye determinar la composición corporal y monitorizar su evolución a lo largo del periodo de tratamiento. La prueba gold standard para el estudio de la composición corporal es la absorciometría de rayos X de energía dual (DEXA), si bien la bioimpedancia eléctrica (BIA) se postula como una alternativa más accesible, barata, rápida y que no irradia. Material y métodos: Se reclutaron secuencialmente a 33 mujeres adolescentes (11,7-16,3 años) diagnosticadas de AN. Se recogieron parámetros clínicos, antropométricos y analíticos, y se realizó BIA y DEXA a la inclusión en el estudio y a la finalización del mismo con separación media de un año, durante la fase de rehabilitación nutricional. Resultados: Se objetivó mejoría significativa a nivel nutricional, reflejada en la composición corporal obtenida mediante antropometría y BIA. El ángulo de fase aumentó significativamente durante el periodo de seguimiento. Una mayor pérdida ponderal se correlacionó con la presencia de amenorrea secundaria y con una menor densidad mineral ósea en columna. Conclusiones: La BIA es una herramienta útil para la valoración y el seguimiento del estado nutricional en pacientes con AN en edad pediátrica. La DEXA sigue siendo imprescindible para conocer la afectación de la densidad mineral ósea. El papel de hormonas como la leptina está aún por determinar.